Investigations into plant biochemical wound-response pathways involved in the production of aphid-induced plant volatiles - Girling, Robbie D (Journal of experimental botany, 2008)
Feeding damage to plants by insect herbivores induces the production of plant volatiles, which are attractive to the herbivores natural enemies. Little is understood about the plant biochemical pathways involved in aphid-induced plant volatile production. The aphid parasitoid Diaeretiella rapae can detect and respond to aphid-induced volatiles produced by Arabidopsis thaliana. When given experience of those volatiles, it can learn those cues and can therefore be used as a novel biosensor to detect them. The pathways involved in aphid-induced volatile production were investigated by comparing the responses of D. rapae to volatiles from a number of different transgenic mutants of A. thaliana, mutated in their octadecanoid, ethylene or salicylic acid wound-response pathways and also from wild-type plants. Plants were either undamaged or infested by the peach-potato aphid, Myzus persicae. It is demonstrated that the octadecanoid pathway and specifically the COI1 gene are required for aphid-induced volatile production. The presence of salicylic acid is also involved in volatile production. Using this model system, in combination with A. thaliana plants with single point gene mutations, has potential for the precise dissection of biochemical pathways involved in the production of aphid-induced volatiles